Team technical performance in elite men`s and women`s T20 cricket - determinants of performance within a match and across a season - Bhardwaj, D.; Dwyer, D. B. (International Journal of Performance Analysis in Sport, 2022)
There have been a small number of analyses of team technical performance in 20-over (T20) cricket that have identified total wickets and runs as critical determinants of match outcome. The present study aimed to extend on these findings by using a wide range of technical performance indicators, a larger sample size, a whole-of-season perspective and an analysis of women`s teams. Team technical performance in 400 and 180 innings of men`s (2017-2021) and women`s (2019-2021) T20 cricket in the professional leagues in Australia were analysed. Batting performance characteristics appear to be more important than bowling characteristics, which is even more pronounced in women`s T20 cricket. The most important bowling characteristic relate to how quickly the first 3 to 5 batters are dismissed. These determinants of match outcome also reflect the characteristics that explain whole-of-season performance. The determinants of performance in women`s T20 cricket are largely the same as in men`s, although there may be an opportunity for some women`s teams to focus on bowling performance as a decisive factor in their match strategy. The findings of this study indicate specific aspects of batting and bowling performance that can influence the goals of training and the design of match strategies.